Validation of GLIM criteria on malnutrition in older Chinese inpatients - Ji, Tong; Li, Yun; Liu, Pan; Zhang, Yaxin; Song, Yu; Ma, Lina (Frontiers in Nutrition, 2022)
Objective: Malnutrition is a nutritional disease which has high incidence and is easily ignored in hospitalized elderly inpatients and can lead to multiple poor prognoses, such as frailty. Early identification and correct evaluation of malnutrition and frailty are essential for improving clinical outcomes in elderly patients. Hence, we aimed to explore the applicability and effectiveness of the Global Leadership Initiative on Malnutrition (GLIM) criterion for identifying undernutrition in elderly inpatients. Methods: In total, 223 participants aged ≥60 years were involved. Nutrition was evaluateded employing the Mini Nutritional Assessment-Full Form (MNA-FF) and GLIM criteria, which adopts a two-step procedure. The first step was to use three different methods for nutritional risk screening: Nutrition Risk Screening 2002, Mini Nutritional Assessment-Short Form (MNA-SF), and the Malnutrition Universal Screening Tool. The second step is to meet the combination of at least one phenotypical criterion and one etiological criterion to diagnose undernutrition. The Clinical Frailty Scale was used to assess frailty. Sensitivity, specificity, Youden index, kappa values, and positive and negative predictive values were measured to test the validity of the GLIM criteria. Logistic regression models were used to assess whether there was a correlation between malnutrition, as defined by the GLIM criteria, and frailty. Results: We found that 32.3-49.8% of inpatients were at risk of malnutrition based on the GLIM diagnosis using the three different screening tools, 19.3-27.8% of patients were malnourished. The GLIM criteria with MNA-SF as the diagnostic validation and MNA-FF as a reference showed high consistency (k = 0.629; P < 0.001), sensitivity (90.5%), and specificity (86.4%). Logistic regression analysis showed that malnutrition, using MNA-SF with the GLIM criteria, was relevant to higher likelihood of frailty (OR=1.887; 95% CI: 1.184-2.589). Conclusion: The incidence of GLIM-defined malnutrition was 19.3-27.8% using different screening tools. The consistency between the GLIM criteria using the MNA-SF and the MNA methods was high. Undernutrition, as diagnosed by the GLIM criteria with MNA-SF, was significantly correlated with frailty. The GLIM criteria with the MNA-SF may be a more reliable malnutrition assessment process in elderly inpatients.